Modelling of the human shoulder as a parallel mechanism without constraints. (June 2016) - Ingram, David; Engelhardt, Christoph; Farron, Alain; Terrier, Alexandre; Müllhaupt, Philippe
Abstract: The synthesis of shoulder kinematics, either for simulation in a model or imitation in a robot, is a challenging task because of the contact between shoulder blade and ribcage. As the shoulder moves, the shoulder blade glides over the ribcage. In kinematic models used to predict musculoskeletal kinetics, the contact is included using equality constraints, creating interdependencies between the kinematic coordinates. Such interdependencies make motion planning complex. Robotic mechanisms often imitate the shoulder's end-effector kinematics but not the gliding shoulder blade architecture. It is only recently that a gliding shoulder blade architecture has been mechanically achieved. The goal of this paper is to propose a novel kinematic parallel model of the shoulder that includes the contact without using constraints. Mechanically, the gliding architecture is replaced with a parallel architecture. A shoulder model with constraints is used to build the parallel model. It is shown that replacing the contact constraints with kinematically equivalent kinematic chains, leads to a 2–3 parallel platform model of the shoulder. The scaffold model and parallel model parameterisations of the shoulder's kinematics are analysed in terms of the forward kinematic map. The coordinate spaces of the kinematic maps are analysed, resulting in three minimal parameterisations. Each minimal parameterisation uses a set of coordinates equal to the number of degrees of freedom. The minimal coordinates are independent and considerably simplify motion planning. Abstract : A novel parallel model of the shoulder girdle and ribcage interaction Contact constraints are replaced with kinematically equivalent kinematic chains. Three sets of seven independent coordinates (dof = 7) parameterise the mechanism. The proposed parameterisations can be used to simplify the motion planning task.